If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = 4x + 6y Solving 42 = 4x + 6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 42 + -4x = 4x + -4x + 6y Combine like terms: 4x + -4x = 0 42 + -4x = 0 + 6y 42 + -4x = 6y Add '-42' to each side of the equation. 42 + -42 + -4x = -42 + 6y Combine like terms: 42 + -42 = 0 0 + -4x = -42 + 6y -4x = -42 + 6y Divide each side by '-4'. x = 10.5 + -1.5y Simplifying x = 10.5 + -1.5y
| (2x^3)+16=0 | | 4y-4+y+28=5+5y+25-3y | | 5(n-18)=10 | | p=10-4y+y^2 | | x^2-72x+100=0 | | 36x^3-15x^2+84x-35=0 | | 9x+12=5x+8 | | 2=t(20-4.9t) | | 6x+7=7x+6 | | 8x-52=2x+14 | | x^2-72x+256=0 | | 180=108(x+18) | | (12+8x)=1 | | (7+3i)-(2+3i)= | | 3y+3x-2=7 | | 1n+9n-10-3= | | 7(9x-3)=4(3x+2) | | 148-4x=60 | | (12-8x)=1 | | 4x-18+x^2-7x=10 | | 7(x+11)=18x+22 | | -2(d+4)-d-3=-3(d+5)+4 | | (5-i)(5+i)= | | -3.2(30)=-96 | | x^2-4x+1=k(x-4) | | x+2y+2z=-1 | | 3m-42-12+12=24 | | 3x+21=5 | | 7(n-8)-(6-n)= | | (3-i)+(1-2i)= | | 9x+12=15x-24 | | v/8=14 |